Pengaruh Daya Tarik dan Reputasi Perusahaan terhadap Minat Melamar Pekerjaan Mahasiswa Manajemen FEB UPN â€œVeteranâ€ Jawa Timur - Rahmadi Wirohikmawan; Kustini Kustini (Universitas Batanghari, 2023)
At present, attention to the creation of a company brand is starting to be used as the basis for a process for employee recruitment or it can be said as a company brand for Employer Branding. Apart from Employer Branding, prospective applicants also often make considerations for the company through the reputation owned by the company when applying for a job. The purpose of this study is to conduct an analysis to determine the effect of Employer Branding and Employer Attractiveness on interest in applying for jobs. The sampling technique in this study uses the Proportionate Stratified Random Sampling technique and uses smartPLS as an analytical tool. Data were obtained from questionnaires distributed to Class of 2017 and 2018 students via google form, with a total sample of 151 respondents. The findings in this study show that Employer Branding has a significant and positive influence on interest in applying for jobs at UPN